La construcción social del personaje en la vida cotidiana: Un estudio poliédrico sobre Letizia Ortiz (La Reina del Pueblo) - Oliva Mederos, Borja (Nómadas. Critical Journal of Social and Juridical Science, 2016)
This innovative and original research seeks to establish a first basis for the scrutiny of the construction of a particular character. This study addresses the presentation on the current Queen of Spain, Letizia Ortiz, from the production of news by journalists and the media, which made the newspapers ABC and El Pais, in addition to the weekly magazine Hello, in a given period, which runs from September to December 2014. all this, developing a model which combines the approaches of political economy, from the structural view, and cultural studies, textual analytical framework. The goal is to unravel the scheme of a polyhedron, taking into account in the process, both the production and the importance of the "channel", so, the message and its support.